Lokalna identyfikacja i samoidentyfikacja mieszkańców północnorosyjskich miast Archangielska i Siewierodwińska (na podstawie danych folklorystyczno-etnograficznych) - Дранникова, Наталья (Studia Rossica Posnaniensia, 2016)
A local population survey based on a specially developed questionnaire was conducted to study the local identity of Arkhangelsk and Severodvinsk in the Arkhangelsk region from 2000 till 2015. The data on folklore and speech obtained allow us to analyze the distinctive features of Arkhangelsk and Severodvinsk citizens’ local identity. The study leads to the conclusion that Arkhangelsk and Severodvinsk's citizens have developed their own local identity, but with different specific characteristics. Arkhangelsk was founded as a traditional town, Severodvinsk during country's urbanization processes.